EFFECTIVENESS OF IMPLEMENTATION OF THE PRINCIPLE OF RECOGNIZING SERVICE USERS FOR NOTARIES BASED ON PERMENKUMHAM NO. 9 YEAR 2017 STUDY IN MALANG CITY - Dian Dombat Pejoreza; Moh Fadli; Rachmi Sulistyarini (RADJA PUBLIKA, 2023)
The presence of a notary in the midst of society is very important, because a notary can provide guarantees of legal certainty related to making authentic deeds. Notaries are burdened with the obligation to implement PMPJ based on Permenkumham No 9 of 2017. This obligation is borne by Notaries as Reporting Parties in reporting suspicious financial transactions of service users as well as a form of protection for Notaries from the dangers of money laundering and steps to support Government programs in eradicating criminal acts money laundering. However, in implementing this principle there are still several notaries who have not implemented it. The problems studied in this study are related to the effectiveness of the implementation of PMPJ based on Permenkumham No. 9 of 2017 on the authority of Notaries in Malang City. The research method used is socio-legal with a sociological approach or looking at the implementation of norms in the field. The results of the study show that notaries in Malang are still found not to have implemented PMPJ based on Permenkumham No. 9 of 2017, PMPJ is considered a Notary. then the implementation is not effective, even though the legal substance has provided rules, the implementation of this article is hampered by several factors, namely the Notary Factor itself which comes from an internal Notary who does not apply it, does not understand the obligation to apply PMPJ (PMPJ) based on Permenkumham No. 9 of 2017, Inadequate facilities, notary's lack of understanding regarding how to control/use the IT system, and there are no strict sanctions from the Ministry of Law and Human Rights against notaries who do not implement PMPJ.